2014
DOI: 10.1016/j.freeradbiomed.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Production of superoxide/H2O2 by dihydroorotate dehydrogenase in rat skeletal muscle mitochondria

Abstract: Dehydrogenases that use ubiquinone as an electron acceptor, including complex I of the respiratory chain, complex II, and glycerol-3-phosphate dehydrogenase, are known to be direct generators of superoxide and/or H2O2. Dihydroorotate dehydrogenase oxidizes dihydroorotate to orotate and reduces ubiquinone to ubiquinol during pyrimidine metabolism, but it is unclear whether it produces superoxide and/or H2O2 directly or does so only indirectly from other sites in the electron transport chain. Using mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Mitochondria can produce superoxide or H 2 O 2 from at least 10 different sites (16,23). Which sites are the major producers in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria can produce superoxide or H 2 O 2 from at least 10 different sites (16,23). Which sites are the major producers in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…1. In order of their maximum capacities, they are as follows: III Qo 4 in complex III (17); I Q (18,19) and II F (20) in complexes I and II; O F , P F , and B F in the 2-oxoglutarate, pyruvate, and branched-chain 2-oxoacid dehydrogenase complexes (16); G Q in mitochondrial glycerol phosphate dehydrogenase (21); I F in complex I (16); E F in ETF/ETF:Q oxidoreductase (22); and D Q in dihydroorotate dehydrogenase (23).…”
mentioning
confidence: 99%
“…Recently, Brand and coworkers [54] separated two components of ROS generation linked to DHO oxidation. In skeletal muscle mitochondria, where the level and activity of the enzyme are so low that DHO-dependent oxygen consumption could not be detected, they were able to detect measurable DHO-dependent H 2 O 2 production.…”
Section: Mitochondrial Ros Productionmentioning
confidence: 99%
“…In skeletal muscle mitochondria, where the level and activity of the enzyme are so low that DHO-dependent oxygen consumption could not be detected, they were able to detect measurable DHO-dependent H 2 O 2 production. Based on sensitivity to specific inhibitors malonate and atpenin A5, it was concluded that the majority of ROS apparently originated from CII [54]. The rate of superoxide/H 2 O 2 generation attributed to DHO DH itself (~20 pmol/min per mg protein) constituted less than 10% of the total rate.…”
Section: Mitochondrial Ros Productionmentioning
confidence: 99%
See 1 more Smart Citation